Art and logic: Godard’s Alphaville as philosophy. - Jones, Andrew (Studies in French Cinema, 2017)
Jean-Luc Godard’s Alphaville: une étrange aventure de Lemmy Caution (1965) constitutes a strikingly brilliant mise en scène of strife between humans and logic. Led by a supercomputer and its scientist-creator, this technocratic city annihilates emotive human creativity. I argue that this dystopian science fiction film is philosophy, precisely because it engages a problem that philosophers also address, namely humanity’s relationship to art and logic. I present this film as an example in defense of the ‘bold thesis’ for film as philosophy developed by Paisley Livingston (2006). Though Livingston argues against this thesis, Aaron Smuts (2009) provides a valiant defense, to which Livingston (2009) responds, stating that only a more relevant example is missing. Supplying this example is the precise intention of this article. To do so, I begin with a discussion of Nietzsche’s The Birth of Tragedy ([1872] 1967), to provide a legitimate philosophical background from which to show how Alphaville not only serves as a thought experiment of prior established philosophy, but also builds upon those ideas to create its own philosophical contribution.